Dung Beetles (Coleoptera: Scarabaeinae) Attracted to Lagothrix lagotricha (Humboldt) and Alouatta seniculus (Linnaeus) (Primates: Atelidae) Dung in a Colombian Amazon Forest - Jorge Ari Noriega (Psyche: A Journal of Entomology)
Dung beetles are among the most important insects in the Neotropics. Some species use a wide range of food sources, whereas other species are highly specialized. This study compares the use of two-primate excrement by an assemblage of dung beetles in a tropical forest in Colombia. Dung of Lagothrix lagotricha and Alouatta seniculus was used to attract beetles. A total of 32 species (47.7% of the species recorded for the area) were found on the two types of excrement studied, demonstrating that primate excrement is an important resource. The niche overlap between both feces is 27.03%, which indicates a high degree of resource specialization. Although these two primate species are found in the same areas, their diets vary greatly to permit a high degree of differentiation in beetle species. A study that includes dung of others primates would create a more complete panorama of resource overlap in the assemblage.